2015
DOI: 10.1530/eje-14-0777
|View full text |Cite
|
Sign up to set email alerts
|

ENDOCRINOLOGY AND ADOLESCENCE: Congenital hypothyroidism: a clinical update of long-term outcome in young adults

Abstract: Congenital hypothyroidism (CH) is the most common congenital endocrine disorder. The early treatment of CH patients has successfully improved the prognosis and management of this disorder. Optimal treatment and management throughout the patient's life, beginning in the neonatal period, are required to ensure long-term health. Affected patients should be offered assessments of associated medical conditions and provided with accurate information about their condition throughout their lives, but particularly duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 110 publications
(126 reference statements)
2
38
0
3
Order By: Relevance
“…Congenital hypothyroidism (CH) had gained its recognition among the endocrinological disorders owing the fact that it's the most common preventable cause of mental retardation in children. (1) Congenital hypothyroidism is defined as thyroid hormone deficiency that exist at birth. It is mainly due to problem in the thyroid gland development (dysgenesis) or due to disruptions in thyroid hormone biosynthesis (dyshormonogenesis).…”
Section: Introductionmentioning
confidence: 99%
“…Congenital hypothyroidism (CH) had gained its recognition among the endocrinological disorders owing the fact that it's the most common preventable cause of mental retardation in children. (1) Congenital hypothyroidism is defined as thyroid hormone deficiency that exist at birth. It is mainly due to problem in the thyroid gland development (dysgenesis) or due to disruptions in thyroid hormone biosynthesis (dyshormonogenesis).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies, in contrast, documented no hearing impairment in patients with screened CH (Francois et al, 1994;Hashemipour et al, 2012). However, only a few studies have focused on neurosensory function of CH patients identified by neonatal CH screening programs and treated early (Leger, 2014) and, therefore, this issue remains still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…The other cause of CH is abnormal hormone production (dyshormonogenesis) (9,10). In this case the thyroid is present, in the normal position (eutopic thyroid), with or without goitre, but it is non functional.…”
Section: Etiologiesmentioning
confidence: 99%